Inhibition of IL-27 signaling regulates chemokine levels and sustains CXCR2 receptor expression on mononuclear cells to improve disease outcomes during gram-negative neonatal sepsis - Annamanedi, Madhavi; Vance, Jordan K.; Robinson, Cory M. (Frontiers in Immunology, 2025)
BackgroundInterleukin-27 (IL-27) is a cytokine that belongs to the IL-6/IL-12 cytokine family with diverse influences on the immune response. Elevated levels of IL-27 cytokine during the neonatal period predispose neonatal mice to more severe infection. Neonatal pups deficient in IL-27 signaling exhibit improved survival and bacterial clearance with reduced systemic inflammation. However, the precise molecular mechanisms that regulate bacterial clearance and the overall immune response in IL-27 receptor a-deficient (KO) mice during neonatal sepsis remain incompletely defined.MethodsAnalysis of the transcriptome of the neonatal spleen during Escherichia coli-induced sepsis in IL-27Rα KO mice identified elevated expression of the chemokine receptor gene CXCR2. Here we further explored the mechanistic insights of the CXCR2/CXCL2 signaling axis limiting the infection in WT and IL-27Rα KO neonatal mice using an n vivo model and ex vivo studies with primary cells.ResultsThe results uncovered that during infection WT neonatal mice fail to increase expression of CXCR2 but upregulate the cognate ligand CXCL2 significantly. Conversely, IL-27Rα KO neonates increase CXCR2 expression significantly in the spleen during infection but fail to upregulate CXCL2 transcripts. Splenocytes isolated form septic neonatal KO mice migrated with superior efficiency towards the chemokine CXCL2 compared to WT counterparts. Surprisingly, we also found that splenic monocytes but not the neutrophils account for higher CXCR2 gene expression in the IL-27Rα KO neonatal mice. Monocytes isolated from the spleens of both WT and IL-27Rα KO neonatal pups confirmed that the concentration of CXCL2 regulates CXCR2 receptor expression. We further demonstrated that with regulated CXCL2 chemokine expression levels, IL-27Ra-deficient neonatal mice had more CXCR2+ mononuclear cells present at the site of infection.ConclusionsOverall, our findings suggest that during infection in the absence of IL-27 signaling, a differential expression of CXCR2 and CXCL2 promotes increased migration of mononuclear cells consistent with improved bacterial clearance and tissue homeostasis. This study defines mechanisms that improve the host response in the absence of IL-27 signaling during neonatal sepsis and reinforces the potential for antagonizing IL-27 as a host-directed therapy for neonatal sepsis.